Nanoemulsified Essential Oil of Melaleuca leucadendron Leaves for Topical Application: In Vitro Photoprotective, Antioxidant and Anti-Melanoma Activities - Lucas Resende Dutra Sousa; Maria Luiza da Costa Santos; Larissa Silva Sampaio; Clarisse Gaëlle Faustino; Mérine Lauriane Loïce Guigueno; Kátia Michelle Freitas; Miriam Teresa Paz Lopes; Gabriela Cristina Ferreira Mota; Viviane Martins Rebello dos Santos; Janaína Brandão Seibert; Tatiane Roquete Amparo; Paula Melo de Abreu Vieira; et al. (MDPI AG, 2024)
Melanoma, primarily caused by solar ultraviolet (UV) radiation, can be prevented by the use of sunscreens. However, the use of synthetic sunscreens raises environmental concerns. Natural compounds with antioxidant photoprotective properties and cytotoxic effects against cancer cells can be promising for the prevention and treatment of melanoma with less environmental effect. This study focuses on Melaleuca leucadendron essential oil (EO) for photoprotection and antitumor applications. EO was hydrodistilled from M. leucadendron leaves with a 0.59% yield. Gas chromatography-mass spectrometry detected monoterpenes and sesquiterpenes. Nanoemulsions were prepared with (NE-EO) and without EO (NE-B) using the phase inversion method, showing good stability, spherical or oval morphology, and a pseudoplastic profile. Photoprotective activity assessed spectrophotometrically showed that the NE-EO was more effective than NE-B and free EO. Antioxidant activity evaluated by DPPH and ABTS methods indicated that pure and nanoemulsified EO mainly inhibited the ABTS radical, showing IC50 40.72 and 5.30 µg/mL, respectively. Cytotoxicity tests on L-929 mouse fibroblasts, NGM human melanocyte, B16-F10 melanoma, and MeWo human melanoma revealed that EO and NE-EO were more cytotoxic to melanoma cells than to non-tumor cells. The stable NE-EO demonstrates potential for melanoma prevention and treatment. Further research is required to gain a better understanding of these activities.